Adverse outcomes post-COVID-19 hospitalization among ESRD patients: A retrospective cohort study in 5 California university medical centers - Marc Reiterman; Andrew I. Chin; Heejung Bang (PLoS ONE, 2025)
Background Individuals with end-stage renal disease (ESRD) hospitalized for COVID-19 may have a higher risk for adverse post discharge events. To investigate these risks, we examined a large database of individuals admitted for COVID-19 and discharged alive, to see if ESRD was independently associated with higher risk for death within 180 days or for 30-day hospital readmission. Methods We retrospectively compared risks for hospital, non-hospital, and overall death within 180 days and 30-day hospital readmission between individuals with and without ESRD. We studied individuals hospitalized with COVID-19 between January 6, 2020 and August 3, 2023, at any of the 5 University of California medical centers and discharged alive. Results Of 11,406 individuals hospitalized with COVID-19 who were discharged alive, 713 (6.3%) had ESRD. Compared to individuals without ESRD, those with ESRD had a significantly higher hazard of hospital and overall death within 180 days post-discharge in the unadjusted analyses, but not in the analyses adjusted for demographic variables, hospitalization period, and comorbid conditions (adjusted Wald chi-square hazard ratio (HR) 1.36, 95% Wald CI 0.78–2.37; adjusted HR 1.05, 95% CI 0.73–1.51, respectively). Those with ESRD did not have a significantly higher hazard of non-hospital death within 180 days post-discharge in either the unadjusted or the adjusted analyses (adjusted HR 0.89, 95% CI 0.55–1.44), but did have a significantly higher hazard of 30-day hospital readmission in both the unadjusted and the adjusted analyses (adjusted HR 1.36, 95% CI 1.14–1.63, p = 0.001). Conclusions ESRD patients hospitalized with COVID-19 had a higher unadjusted risk of hospital and overall death within 180 days and of 30-day hospital readmission than individuals without ESRD. After adjusting for demographic factors, hospitalization period, and comorbidities, presence of ESRD was not found to significantly increase the risk for hospital, non-hospital, or overall death within 180 days post-discharge, but was found to significantly increase the risk of 30-day hospital readmission.